Left atrial appendage function by strain predicts subclinical atrial fibrillation in patients with cryptogenic stroke/TIA. (14th October 2021) - Saberniak, J; Skrebelyte-Strom, L; Orstad, E.B; Solberg, M.G; Hilde, J.M; Ronning, O.M; Kjekshus, H; Steine, K
Abstract: Background: Left atrial (LA) function by strain has shown to be promising to predict clinical atrial fibrillation (AF) in patients with cryptogenic stroke/TIA. However, there is little knowledge, if this novel method may prospectively predict subclinical AF (SCAF) and moreover, if left atrial appendage (LAA) function by strain and mechanical dispersion may be more sensitive to improve prediction of SCAF. Purpose: The aim of the present study was to investigate if LA and LAA function by strain could improve the prediction of SCAF in patients at risk. Methods: In this prospective study (mean follow-up 859±226 days), 185 patients with cryptogenic stroke/TIA, mean age 68±13 years, 33% female and no history of clinical AF or SCAF, were included. All participants underwent 2D and 3D transesophageal and transthoracic echocardiography in sinus rhythm after index cryptogenic stroke/TIA (mean 5±3days). LAA and LA functions by phasic strain, including reservoir strain (Sr), conduit strain (Scd) and contraction strain (Sct) and mechanical dispersion of Sr were assessed. SCAF episodes were detected by cardiac monitoring during follow up (mean 257±273 days). Results: LAA function by strain was decreased in those with SCAF (60/32% of all patients) compared to those without: Sr: 19.2±4.5% vs. 25.6±6.5% (p<0.001), Scd: −11.0±3.1% vs. −14.4±4.5% (p<0.001), Sct: −7.9±4.0% vs. −11.2±4% (p<0.001), respectively, while mechanical dispersion by Sr strain was increased, 34±24ms vs. 26±20ms (p=0.02). However, LA function by strain and mechanical dispersion did not differ in patients with SCAF compared to patients without. By ROC analyses, LAA strain and mechanical dispersion were highly significant in prediction of SCAF. LAA reservoir strain showed the best AUC of 0.80 (95% CI 0.73–0.87) with a cut-off value of 22.2%, sensitivity of 80%, and specificity of 73%, p<0.001. (Figure) Conclusions: For the first time, we showed, that left atrial appendage function by strain and mechanical dispersion predicts SCAF, as opposed to left atrial function. Left atrial appendage function by strain may be useful in risk prediction in patients at considerable AF risk. FUNDunding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Department of Cardiology, Akershus University Hospital, Oslo/Lørenskog, Norway